The method of integrated kinetics and its applicability to the exo-glycosidase-catalyzed hydrolysis of p-nitrophenyl glycosides. (14th August 2015) - Borisova, Anna S.; Reddy, Sumitha K.; Ivanen, Dina R.; Bobrov, Kirill S.; Eneyskaya, Elena V.; Rychkov, Georgy N.; Sandgren, Mats; Stålbrand, Henrik; Sinnott, Michael L.; Kulminskaya, Anna A.; Shabalin, Konstantin A.
Abstract: In the present work we suggest an efficient method, using the whole time course of the reaction, whereby parameters k cat, K m and product K I for the hydrolysis of a p- nitrophenyl glycoside by an exo -acting glycoside hydrolase can be estimated in a single experiment. Its applicability was demonstrated for three retaining exo -glycoside hydrolases, β-xylosidase from Aspergillus awamori, β-galactosidase from Penicillium sp. and α-galactosidase from Thermotoga maritima (TmGalA). During the analysis of the reaction course catalyzed by the TmGalA enzyme we had observed that a non-enzymatic process, mutarotation of the liberated α-d -galactose, affected the reaction significantly. Graphical abstract: Highlights: Simple analysis of integrated kinetics provides k cat, K m, K I in a single experiment. Mutarotation of the liberated carbohydrate product affects the reaction course. Temperature dependence of galactose mutarotaion is characterized. Inhibition by α- and β-galactoses is distinguishable by temperature change.